The Effects of Accounting Language and Staff Capacity on Local Government Authorities’ Financial Reporting Quality - Matekele, Charles K; Mbogela, Cosmas S.; Keregero, Chirongo M. (SEISENSE Journal of Management, 2025)
Purpose- This study employs institutional and cognitive load theories to explore and understand how accounting staff capacity and accounting language capacity relate to local government authorities' (LGAs’) financial reporting quality in Tanzania.Design/Methodology- Data were gathered from 126 LGAs represented by 225 internal auditors and accountants using a survey instrument. To test the hypotheses, partial least squares structural equation modelling (PLS-SEM) was used.Findings- Results establish that financial reporting quality is significantly explained by accounting staff capacity and accounting language capacity. This is evidenced by the existence of positive and significant effects of accounting staff capacity and accounting language capacity on LGAs' financial reporting quality.Practical Implications-Since accounting language and staff capacity significantly influence financial reporting quality in LGAs, governments of developing countries must vigorously promote and encourage professional development, enhance financial reporting and communications skills, and generally be an excellent example of encouraging the capacities of accountants and auditors. In doing so, the quality of financial reporting among LGAs will be guaranteed.